О кривизне контактных структур и слоений - Круглов, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Using the result of D. Hardorp on the existence of total foliations, we prove that each closed orientable 3D manifold has a strong saddle foliation. We also prove that any contact structure with vanishing Euler class admits an uniformization.